Interactive Learning Media Loaded with Human Growth and Development Materials in Science Learning in Elementary Schools that is Decent and Practical: Media Pembelajaran Interaktif, IPA, Articulate Storyline 3 - Safti Putri, Nur; Hendrik, Maulina; Romadhon , Romadhon (EduStream: Jurnal Pendidikan Dasar, 2024)
Interactive learning media is needed to improve the quality of science learning in elementary schools. The purpose of this study is to produce interactive science learning media for growth and development materials in grade 3 of elementary school. This research method is in the form of research and development (R&D) with the ADDIE development model. This article focuses on the "D&D" stage of design  and development.  The subjects of the study were 27 grade 3 elementary school students. Data collection techniques are interviews and questionnaires. The data collection instruments are in the form of expert validation questionnaires and student and teacher response questionnaires. The data analysis technique by calculating the average and percentage of the questionnaire score then converts it into qualitative data for interpretation. The results of the study showed that media expert 1 gave a score of 88% (Very Valid), media expert 2 gave a score of 98% (Very Valid), and material expert 88% (Very Valid). The results of the one to one and small group tests  show a percentage of 100% (Very Practical). The teacher's response questionnaire obtained a score of 100% (Very Practical). In conclusion, interactive learning media to teach growth and development material in science lesson content in grade 3 elementary school is declared feasible and practical to use.